2021
DOI: 10.3389/fpsyg.2021.760258
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the Cost of Being the Boss: Authentic Leadership Suppresses the Effect of Role Stereotype Conflict on Antisocial Behaviors in Leaders and Entrepreneurs

Abstract: What drives entrepreneurs to engage in antisocial economic behaviors? Without dismissing entrepreneurs’ agency in their decision-making processes, our study aims to answer this question by proposing that antisocial economic behaviors are a dysfunctional coping mechanism to reduce the psychological tension that entrepreneurs face in their day-to-day activities. Further, given the overlap between the male gender role stereotype and both leader and entrepreneur role stereotypes, this psychological tension should … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 80 publications
1
8
0
Order By: Relevance
“…Some may express concerns that our leadership manipulation was non-significant for women in work session 1. However, this finding aligns with prior results showing that male leaders displaying an authentic leadership style do not influence male and female followers equally (Eagly, 2005;Monzani et al, 2015Monzani et al, , 2021.…”
Section: Strengths Limitations and Future Research Directionssupporting
confidence: 90%
See 1 more Smart Citation
“…Some may express concerns that our leadership manipulation was non-significant for women in work session 1. However, this finding aligns with prior results showing that male leaders displaying an authentic leadership style do not influence male and female followers equally (Eagly, 2005;Monzani et al, 2015Monzani et al, , 2021.…”
Section: Strengths Limitations and Future Research Directionssupporting
confidence: 90%
“…In line with prior theorizing (Eagly, 2005) and studies exploring gender assigned at birth and authentic leadership (Woolley et al, 2011;Monzani et al, 2015Monzani et al, , 2021, significant differences in the expected direction between leadership style conditions were found for men [Wilks' = 0.82, F(4,66) = 3.51, p < 0.05, partial η 2 = 0.17], but not for women [Wilks' = 0.98, F(4,148) = 0.65, n.s.]. For work session 2, estimated marginal means for all four authenticity dimensions were higher in the authentic leader condition for all participants, regardless of their gender assigned at birth [Wilks' = 0.96, F(4,220) = 2.465, p < 0.05, partial η 2 = 0.04].…”
Section: Preliminary Checksmentioning
confidence: 53%
“…As several of the studies in this Special Issue have shown (e.g., Henningsen et al, 2022; Süssenbach & Carvacho, 2022), factors within the actors, the recipients and observers can increase gender‐stereotypical thinking, behaviors, and its consequences. Yet, further external factors affect gender‐role stereotyping (March et al, 2016; Monzani et al, 2021; Obioma, Jaga, et al, 2022). Factors studied in this Special Issue include, amongst others, the cultural context and the stereotyped content.…”
Section: Boundary Conditions For Affecting and Addressing Gender‐role...mentioning
confidence: 99%
“…However, this solution also goes along with drawbacks, as female leaders are expected to show transformational leadership behavior and thus, do not receive additional recognition when acting transformational like male leaders do ( Hentschel et al, 2018 ). Therefore, the present study focuses on a positive leadership style that includes both communal and agentic aspects and thus, is more ambiguous regarding its fit to gender role stereotypes; precisely on authentic leadership ( Monzani et al, 2021 ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Thus, female leaders might benefit from additional empirical insights that can extend or complement RCT while honoring its core propositions. For example, a recent study extended RCT theory to the field of entrepreneurship, attempting to find ways to reduce the societal pressures that elicit antisocial behaviors in female leaders and entrepreneurs (Monzani et al, 2021). In the present study, we propose complementing RCT with insights from the Social Identity Model of Leadership (SIMOL; Hogg, 2001).…”
Section: Introductionmentioning
confidence: 99%